An Early Increase of Blood Leukocyte Subsets in Aneurysmal Subarachnoid Hemorrhage Is Predictive of Vasospasm - Bacigaluppi, Susanna; Ivaldi, Federico; Bragazzi, Nicola L.; Benvenuto, Federica; Gallo, Fabio; D'Andrea, Alessandro; Severi, Paolo; Uccelli, Antonio; Zona, Gianluigi (Frontiers in Neurology, 2020)
Object: Vasospasm is a severe complication in patients with aneurysmal subarachnoid haemorrhage (aSAH) and cannot be reliably predicted. Its pathophysiology remains elusive with the current body of evidence suggesting inflammation as one of the main driving forces. We here aimed to analyse circulating immune cell subsets over time in patients with aSAH with or without vasospasm.We performed a prospective observational study recruiting patients with spontaneous aSAH. Peripheral blood withdrawn at pre-specified time-points after aSAH, day 0, days 3-4, 6-8, 10-11, 13-15 and 18-21. Flow-cytometry analysis, cell blood counts and laboratory and diagnostic parameters were performed. Patients were monitored by trans-cranial doppler for vasospasm as well as by advanced imaging and divided into a group with (VS) and without vasospasm VS (NVS)We included 42 patients, 21 with VS and 21 without VS (NVS). An early significant increase at day 0 in platelet, leukocyte, neutrophil, lymphocyte, NK lymphocyte, monocyte and CD++ CD16 -DR + monocyte counts was found in patients with later ensuing vasospasm. The early differences in platelets, leukocytes, lymphocytes and NK lymphocytes remained significant on multivariate analysis.An early increase of immune cellular subsets in aSAH may contribute to predict VS.